Cardiac arrest and atrial fibrillation in a patient after hump-nosed pit viper (Hypnale hypnale) bite. (15th June 2018) - Namal Rathnayaka, R.M.M.K.; Nishanthi Ranathunga, P.E.A.; Ranaweera, Janaka; Jayasekara, Krishantha; Kularatne, S.A.M.
Abstract: A 42-year-old previously healthy male patient died 16 days after a proven hump-nosed pit viper ( Hypnale hypnale ) envenoming due to multi-organ failure. On admission he had cardiac arrest that recovered from cardiopulmonary resuscitation then developed atrial fibrillation which was reverted to normal rhythm by application of synchronized electrical cardioversion. He also had persistent coagulopathy and thrombotic microangiopathy comprising the triad of microangiopathic haemolysis, acute kidney injury and thrombocytopenia. This is the second reported case with cardiac complications following hump-nosed pit viper bites in Sri Lanka. Highlights: A case report of hump-nosed pit viper ( Hypnale hypnale ) bite is presented. History, examination, laboratory and autopsy findings of the patient are included. A cardiac involvement following Hypnale hypnale bite in Sri Lanka is described.